Evaluating the sustainability of forest utilization in the protected areas of Mandalagiri Forest, West Java, Indonesia - FAIZAL MUTAQIN; DODIK RIDHO NURROCHMAT; BAMBANG SUPRIYANTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mutaqin F, Nurrochmat DR, Supriyanto B. 2023. Evaluating the sustainability of forest utilization in the protected areas of Mandalagiri Forest, West Java, Indonesia. Biodiversitas 24: 2745-2755. Forests have tangible and intangible benefits, which can be included accordingly in vital sectors for development. Currently, forest management mainly focuses on timber extraction while paying less attention to Non-Timber Forest Products (NTFPs) and environmental services. It causes timber production to decrease yearly and a decline in the forestry sector's contribution to the state's income. The Forest area covers more than 60% of the Indonesian land surface, but the sector's contribution to the national Gross Domestic Product (GDP) in 2022 was only 0.6%. It implies that there is a need for more efforts to increase the productivity of the forestry sector and its contribution to the national economy. One of the institutions that have the potential to optimize the utilization of forest areas is the Mandalagiri Forest Management Resort, West Java, Indonesia. Cultivated commodities come from NTFPs (pine gum and coffee) as the primary commodities. This area's management applies a social forestry system by cooperating with the community. These ongoing activities have not been able to significantly contribute to the regional stakeholders (government) or the community. Therefore, this study aimed to create an efficient concept of optimal forest utilization in running a business and managing social problems and describes the results of identifying enabling factors to encourage the application of multi-business forestry in protected areas. The feasibility of sustainable forest utilization was measured through an analysis of social acceptance, financial analysis (Net Present Value, Benefit-Cost Ratio, and Internal Rate of Return), and an analysis of the ecological feasibility of the model that has been built. The research ended with identifying enabling factors from a policy, social and environmental perspective. This study concluded that forestry multi-business could be carried out in this location because it can potentially restore biophysical conditions and support forest and land rehabilitation efforts. In addition, various selected plant species can contribute to strengthening the soil, reducing the rate of surface water run-off, and enriching the crop. Financially, the forest multi-businesses are feasible to apply with NPV>0, BCR>1, and IRR>I. Ecologically, these schemes can reinforce biophysical conditions.